The beta-lactamase secreted by the antarctic psychrophile Psychrobacter immobilis A8. - Feller, G (1995)
A class C beta-lactamase has been purified from the culture supernatant of the antarctic psychrophile Psychrobacter immobilis A8. This psychrophilic beta-lactamase displays a low level of thermal stability and a low optimal temperature of activity. In contrast to other cold-adapted enzymes, its level of specific activity is not higher than that of mesophilic class C beta-lactamases.